2023
DOI: 10.3390/vetsci10020168
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Vertebral Length-to-Height Ratio, a Promising Parameter to Predict the Vertebral Heart Score in Normal Welsh Corgi Pembroke Dogs

Abstract: The vertebral heart score (VHS) is the sum of the ratio of the cardiac dimensions to the number of thoracic vertebrae, starting from the fourth thoracic vertebra (T4) to the intervertebral disk space (IVS). Breed-specific VHSs, in most cases, were different from the original reference value. Characteristics of the thoracic vertebrae and IVS may influence this variation. This study was conducted to investigate the characteristics of the T4 and IVS on the thoracic radiographs of Corgis in comparison with other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Considering the effect of sex on vertebral parameters, our results showed that sex did not affect the vertebral length, height, and length/height ratio of T4, L2, L5, and L7. Our results are consistent with previous results reported in dogs showing that there is no significant difference in the T4 length and height between the sexes [23]. However, these results are in contrast to those found in humans [24], namely that males have an increased vertebral height compared to women [24].…”
Section: Discussionsupporting
confidence: 92%
“…Considering the effect of sex on vertebral parameters, our results showed that sex did not affect the vertebral length, height, and length/height ratio of T4, L2, L5, and L7. Our results are consistent with previous results reported in dogs showing that there is no significant difference in the T4 length and height between the sexes [23]. However, these results are in contrast to those found in humans [24], namely that males have an increased vertebral height compared to women [24].…”
Section: Discussionsupporting
confidence: 92%